Marketing Strategy Analysis Based on Segmenting, Targeting, and Positioning in Hospital - Kartika Ningsih; Tri Ani Marwati (Universitas Ahmad Dahlan, 2023)
Background: There is a fluctuating trend related to the number of patient visits at Nur Hidayah Hospital, Bantul, so it is necessary to formulate the right Segmentation, Targeting, and Positioning (STP) in order to increase inpatient and outpatient visits and achieve standard inpatient service indicators. The purpose of this study is to analyze the marketing strategy of Nur Hidayah Hospital based on STP. Method: This study follows a descriptive qualitative design. The key informants in this study were the general director and the marketing manager of the hospital, and the triangulation informants in this study were medical officers and patients. Results: The results revealed that the segmenting was based on demographics with females or housewives with secondary education levels or lower as the highest number of service users. Based on the geographical characteristics, a significant number of service users were those living in Ring 1, an area within a radius of 0-10 km from the hospital. Targeting has been conducted well as seen by the number of patients that reached 6,500 service users within a year. Positioning was related to the availability of surgeons, a relatively short surgery duration, and services that are good, friendly, and neat that make patients feel like they are treated by their own families. Conclusion: The market segment, targeting, and positioning was good, but not fulfilled enough. Nur Hidayah Hospital should evaluate community responses regarding what is needed to fulfill target community.